Chronic Binge Alcohol-Associated Differential Brain Region Modulation of Growth Factor Signaling Pathways and Neuroinflammation in Simian Immunodeficiency Virus-Infected Male Macaques. (19th July 2019) - Maxi, John K; Mercante, Don; Foret, Brittany; Oberhelman, Sarah; Ferguson, Tekeda F; Bagby, Gregory J; Nelson, Steve; Amedee, Angela M; Edwards, Scott; Simon, Liz; Molina, Patricia E
Abstract : In chronic alcohol-administered, SIV-infected macaques, differential brain region susceptibility to inflammatory, viral, neurotropic, and alcohol insults was associated with neurocognitive impairment. In the prefrontal cortex, suppression of growth factor signaling may be an important neuropathological mechanism, while inflammatory processes play a more important role in the caudate and hippocampus. Abstract: Aims: Microarray analysis of hippocampal tissue from chronic binge alcohol (CBA)-administered, simian immunodeficiency virus (SIV)-infected male macaques identified altered immune response and neurogenesis as potential mechanisms underlying cognitive deficits in macaques. This study investigated the differential brain region associations between markers of neuroinflammation and growth factor signaling with microtubule-associated protein 2 (MAP2) expression. Methods: Adult male rhesus macaques were administered CBA (13–14 g EtOH/kg/week, n = 8) or sucrose (SUC, n = 7) beginning 3 months prior to SIV infection and continued until animals reached end-stage disease criteria (3–24 months post infection). Expression of inflammatory cytokines, growth factors, and viral loads were determined in the prefrontal cortex (PFC), caudate (CD), and hippocampus (HP). Brain-derived neurotropic factor (BDNF) expression and phosphorylation of intracellular kinases downstream of BDNF were investigated in the PFC. Results: Our results show reduced MAP2 expression in the PFC of longer-surviving, CBA/SIV macaques. BDNF expression was most closely associated with MAP2 expression in the PFC. In the caudate, significant positive associations were observed between MAP2 and BDNF, time to end-stage and set-point viral load and significant negative associations for CBA. In the hippocampus, positive associations were observed between MAP2 and inflammatory cytokines, and negative associations for brain viral load and CBA. Conclusions: CBA differentially affects growth factor and inflammatory cytokine expression and viral load across brain regions. In the PFC, suppression of growth factor signaling may be an important neuropathological mechanism, while inflammatory processes may play a more important role in the CD and HP.